The Types and Causes of Anxiety in EFL Students during Proposal Seminar Presentations - Achmad, Diana; Abdul Samad, Iskandar; Muslem, Asnawi; Qismullah Yusuf, Yunisrina; Siti Sarah Fitriani; Thara Hendri Safitri; Linville, Heather (Universitas Jambi, Indonesia, 2024)
A proposal seminar presentation is one of the compulsory activities that university students must undertake before writing their thesis. This usually causes anxiety for students because they have to present their research proposals in front of lecturers as reviewers. Therefore, this study aims to identify the types and causes of speaking anxiety among English Education Department students at Universitas Syiah Kuala during their proposal seminar presentations. This study used a descriptive qualitative design in which questionnaires, interviews and observation were employed as research instruments. The data were collected from ten students who were presenting their research proposals. The analysis, involving percentages and transcript examination, revealed three types of speaking anxiety: test anxiety, communication apprehension, and fear of evaluation. Test anxiety emerged as the most prevalent type. Additionally, the study identified three primary factors contributing to speaking anxiety: fear of making mistakes, insufficient knowledge, and low self-confidence.